Training via Sandwich Education: How Stressed is the Counsellor Trainee? - Theresa Antwi; Patricia Amos; Stephen Antwı-danso; John Rye Adade (e-Kafkas Eğitim Araştırmaları Dergisi)
The voluminous study nature and the intensive structure of sandwich study mode masters-level counselling programmes might pose various unascertained stress levels to counsellor trainees. With a descriptive cross-sectional study design and a census survey, this study used the University Stress Scale (USS) to determine the prevailing stress levels among 92 Master of Education (MEd) counsellor trainees in a Ghanaian university. The study employed means with standard deviation and t-test to analyse the data set. The findings of the study indicated that counsellor trainees reported stress levels that predicted significant psychological distress. Also, some perceived stressors emerged as the major predictors of significant psychological distress. However, there were no statistical differences in the stress levels of men and women, those below 35 years and those that were 35 years and above, and, those in year one and those in year two of their studies. Thus, the study recommended that a stress-reducing and positive-coping strategy guide, encompassing age, gender and years in training, would improve the mental health of sandwich mode masters-level counsellor trainees. The study also recommended that the counsellor trainees practice self-awareness, self-assessment, and self-assistive strategies to identify and cope with their stressors and seek psychological help when necessary. The study suggested that university authorities and counsellor educators consider a Sandwich Hybrid and Blended Learning environment for counsellor training through a sandwich education mode.